2017
DOI: 10.1016/j.atherosclerosis.2017.05.026
|View full text |Cite
|
Sign up to set email alerts
|

Monocyte inflammatory profile is specific for individuals and associated with altered blood lipid levels

Abstract: Our data indicates that priming of all monocytes to an inflammatory state occurs in individuals with a perturbed lipid profile, overriding the normal functional distinction attributed to the different monocyte subsets. As such, all monocytes may be important in CVD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
55
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(61 citation statements)
references
References 48 publications
5
55
0
1
Order By: Relevance
“…*p < 0.05, **p < 0.01, ***p < 0.001, Student's unpaired t test. (2020) 10:4397 | https://doi.org/10.1038/s41598-020-61022-1 www.nature.com/scientificreports www.nature.com/scientificreports/ alterations, as well as environmentally linked changes in monocytes (with factors such as viral infections, microbiota composition, serum lipid levels, and lifestyle choices) [34][35][36][37][38][39][40][41][42][43] .…”
Section: Discussionmentioning
confidence: 99%
“…*p < 0.05, **p < 0.01, ***p < 0.001, Student's unpaired t test. (2020) 10:4397 | https://doi.org/10.1038/s41598-020-61022-1 www.nature.com/scientificreports www.nature.com/scientificreports/ alterations, as well as environmentally linked changes in monocytes (with factors such as viral infections, microbiota composition, serum lipid levels, and lifestyle choices) [34][35][36][37][38][39][40][41][42][43] .…”
Section: Discussionmentioning
confidence: 99%
“…Yvan-Charvet et al [ 23 ] and Esteve et al [ 24 ] revealed the idea that the HDL levels are related to the cytokine levels. On the one hand, increased HDL levels can cause decreased circulating levels of proinflammatory cytokines, such as interleukin 6 (IL-6) and tumor necrosis factor (TNF-α) [ 25 ] . On the other hand, elevated HDL levels can produce increased levels of anti-inflammatory cytokines, such as IL-10 [ 26 ] .…”
Section: Discussionmentioning
confidence: 99%
“…In response to TLR agonists, classical monocyte subsets are the most producers for TNFα, IL-6 and IL-1β and non-classical monocytes are the lowest producers [ 50 ]. Nevertheless, the classical monocytes produce high levels of IL-10 and low levels of TNF-α whereas intermediate monocytes mainly releasing TNF-α have been controversially reported [ 52 , 53 ]. In this study, mAb P-3E10 induced IL-6, IL-10 and TNF-α production in monocytes.…”
Section: Discussionmentioning
confidence: 99%